2020
DOI: 10.1101/2020.10.16.343053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil disturbance affects plant growth via soil microbial community shifts

Abstract: Recent advances in climate research have discovered that permafrost is particularly vulnerable to the changes occurring in the atmosphere and climate, especially in Alaska where 85% of the land is underlain by mostly discontinuous permafrost. As permafrost thaws, research has shown that natural and anthropogenic soil disturbance causes microbial communities to undergo shifts in membership composition and biomass, as well as in functional diversity. Boreal forests are home to many plants that are integral to th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The link between host phylogeny and ARG abundance demonstrates how a loss of Firmicutes and enrichment of Proteobacteria as a result of community shifts could increase the abundance of ARGs within a community. Although we cannot say from this specific dataset of cultured isolates which taxa are enriched across FPES sites, previous analyses conducted on uncultured metagenomic data from across 48 FPES cores in Seitz et al, 2020 identified over-representation of the phylum Proteobacteria in the disturbed cores and of the order Bacillales in undisturbed cores [ 24 ]. This enrichment in the metagenomic data parallels the enrichment of these taxa in this cultured subset of the community.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The link between host phylogeny and ARG abundance demonstrates how a loss of Firmicutes and enrichment of Proteobacteria as a result of community shifts could increase the abundance of ARGs within a community. Although we cannot say from this specific dataset of cultured isolates which taxa are enriched across FPES sites, previous analyses conducted on uncultured metagenomic data from across 48 FPES cores in Seitz et al, 2020 identified over-representation of the phylum Proteobacteria in the disturbed cores and of the order Bacillales in undisturbed cores [ 24 ]. This enrichment in the metagenomic data parallels the enrichment of these taxa in this cultured subset of the community.…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes fosfomycin thiol transferase that confers resistance to an antibiotic derived from secondary metabolites produced by soil-dwelling bacteria including Streptomyces and pseudomonads [ 42 ]. Both Streptomyces and pseudomonads have been found to be abundant in FPES metagenomic datasets [ 24 ] highlighting the taxonomic potential for the production of fosfomycin at this locale. This potential along with the high abundance of fosB found in this study is suggestive of the selective advantage encoding antibiotic inactivating enzymes may have in competing against antibiotic producing bacterial taxa in the soil community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This research was supported by the Alaska BLaST program, the Institute of Arctic Biology, and Alaska INBRE. The content of this manuscript has previously appeared as a preprint in bioRxiv ( Seitz et al, 2020 ).…”
mentioning
confidence: 99%